Жизнь Арсеньева - Бунин Иван Алексеевич (Бриллиантовая коллекция, 2006)
Экземпляры: АБ (20200109) / Инвентарный номер: 47825 / Цена: 77.90 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Б 91 / ББК: 84(2Рос=Рус)1